Friends, lovers, and the big terrible thing : [large type] a memoir - Perry, Matthew, 1969- (Thorndike Press, a part of Gale, a Cengage Company, 2022)
Perry takes readers behind the scenes of the sitcom Friends-- and into his struggles with addiction. Vividly detailing his lifelong battle with alcoholism and drugs, he examines what fueled it despite seemingly having it all: the desire for recognition that drove him, the void inside him that could not be filled, and the peace he's found in sobriety. -- adapted from back cover